Inferior Pancreaticoduodenal Artery Aneurysm Related with Groove Pancreatitis Persistently Repeated Hemosuccus Pancreaticus Even After Coil Embolization - Hori, Tomohide (Am J Case Rep, 2019)
Patient: Male, 58 Final Diagnosis: Inferior pancreaticoduodenal artery aneurysm Symptoms: Bleding Medication: — Clinical Procedure: Pancreaticoduodenectomy Specialty: Surgery OBJECTIVE: Rare disease BACKGROUND: Aneurysm of the inferior pancreaticoduodenal artery (IPDA) is rare among visceral artery aneurysms. Aneurysm and/or pancreatitis may have a causal relation with hemosuccus pancreaticus (HP). HP causes an obscure bleeding in the digestive tract, and this rare disease may lead to life-threatening condition. Although interventional radiology is generally employed as the initial treatment for visceral aneurysms, aneurysmic recanalization is a critical problem. CASE REPORTS: A 58-year-old male was incidentally diagnosed as groove pancreatitis, and his pancreatitis was successfully treated by conservative management. One year later, an IPDA aneurysm was detected in image studies. Gastrointestinal bleeding was objectively observed, and a diagnosis of asymptomatic HP was made. Arteriopancreatic duct fistula was suspected, but was not identified. Coil embolization was successfully completed. Six months later, he suffered a relapse of HP, and visited our emergency unit. Pseudocystic lesion around metallic coils were confirmed. Subtotal stomach-preserving pancreaticoduodenectomy without any extended resections was performed. Intentional dissections of nerve plexuses and lymph nodes were all waived. Even a pancreatography of the resected specimen did not clarify his arterio-pancreatic duct fistula. He was discharged at postoperative day 10, and smoothly returned to his work. CONCLUSIONS: Pancreatic juice-related complications after advanced pancreaticoduodenectomy for malignancies are often intractable. However, simple pancreaticoduodenectomy which omits extended resections and intentional dissections is safe and feasible for benign diseases. After the initial interventional radiology for pancreatic aneurysms, an elective pancreatic surgery should be considered to avoid unwanted recanalization and refractory HP.